2007
DOI: 10.1007/s00442-007-0870-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of floral traits on the reproductive success of epiphytic and terrestrial tropical orchids

Abstract: We investigated the relationship between habit, population size, floral traits and natural fruit set levels of 23 tropical orchid species of south-east Bangladesh. We showed that epiphytic orchids had lower fruit set levels than terrestrial species and that habit explained much of the variation in floral traits among the orchids. We compared our results with data from 76 other species occurring in the study area and hypothesize that a suite of floral and population characteristics present in tropical orchids c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 66 publications
0
23
0
1
Order By: Relevance
“…As in most orchids [24,25], fruit set in D. ferruginea is generally pollen-limited and an increase in pollinator visits translates into increased fecundity [21], allowing us to use relative visitation rates as a proxy for fitness.…”
Section: Methodsmentioning
confidence: 99%
“…As in most orchids [24,25], fruit set in D. ferruginea is generally pollen-limited and an increase in pollinator visits translates into increased fecundity [21], allowing us to use relative visitation rates as a proxy for fitness.…”
Section: Methodsmentioning
confidence: 99%
“…Larger flowers may represent more powerful signals to pollinators than smaller ones and may be favored by selection in a similar manner to flower production (Waite et al 1991 ;Murren and Ellison 1996 ;Tremblay et al 2005) . The recent comparative study of Huda and Wilcock (2008) confirmed that tropical nectarless orchids have displays with larger flowers than their rewarding counterparts, irrespective of their habit.…”
Section: Large Floral Displaysmentioning
confidence: 68%
“…Huda & Wilcock [27] indicated that the low fruit set that occurs in tropical epiphytic orchids is associated with the combined effects of a suite of floral and population characteristics, such as rewardless flowers, non-sectile pollinia, self-incompatibility, and small population sizes. Our investigation has indicated that there are at least two mechanisms of promoting fruit set in the food-deceptive epiphytic orchids in tropical regions : …”
Section: Discussionmentioning
confidence: 99%